Management of Drug-Drug Interactions Between Long-Acting Cabotegravir and Rilpivirine and Comedications With Inducing Properties: A Modeling Study. (15th November 2022) - Bettonte, Sara; Berton, Mattia; Stader, Felix; Battegay, Manuel; Marzolini, Catia
Abstract: Background: Long-acting (LA) intramuscular cabotegravir and rilpivirine are prone to drug-drug interactions (DDI). However, given the long dosing interval, the conduct of clinical DDIs studies with LA antiretrovirals is challenging. We performed virtual clinical DDI studies using physiologically based pharmacokinetic (PBPK) modeling to provide recommendations for the management of DDIs with strong or moderate inducers such as rifampicin or rifabutin. Methods: Each DDI scenario included a cohort of virtual individuals (50% female) between 20 and 50 years of age with a body mass index of 18–30 kg/m 2 . Cabotegravir and rilpivirine were given alone and in combination with rifampicin or rifabutin. The predictive performance of the PBPK model to simulate cabotegravir and rilpivirine pharmacokinetics after oral and intramuscular administration and to reproduce DDIs with rifampicin and rifabutin was first verified against available observed clinical data. The verified model was subsequently used to simulate unstudied DDI scenarios. Results: At steady state, the strong inducer rifampicin was predicted to decrease the area under the curve (AUC) of LA cabotegravir by 61% and rilpivirine by 38%. An increase in the dosing frequency did not overcome the DDI with rifampicin. The moderate inducer rifabutin was predicted to reduce the AUC of LA cabotegravir by 16% and rilpivirine by 18%. The DDI with rifabutin can be overcome by administering LA cabotegravir/rilpivirine monthly together with a daily oral rilpivirine dose of 25 mg. Conclusions: LA cabotegravir/rilpivirine should be avoided with strong inducers but coadministration with moderate inducers is possible by adding oral rilpivirine daily dosing to the monthly injection. Abstract : Drug-drug interactions (DDI) between strong inducers and long-acting (LA) cabotegravir and rilpivirine cannot be overcome. However, DDIs with moderate inducers can be managed by administering LA cabotegravir and rilpivirine monthly together with an oral rilpivirine daily dose of 25 mg.